ENT 530 Social Media Portfolio : C&J iWorkout / Clement Anak Rowin - Rowin, Clement (2019)
The target market for C&J iWorkout is people who want to reach a good fitness level in their life, people who want to lose weights, people who want to gain muscles and others that related to fitness in Puncak Alam area. C&J iWorkout provide a personal training service to the clients and help the clients to reach their fitness goals.